MULTILINGUALISM IN EDUCATION: THE ROLE OF FIRST LANGUAGE - Rogers, Angela (Indonesian Journal of Applied Linguistics, 2014)
Abstract: This paper discusses the possibilities and effects of different language policies in schools around the world, based on recent research on second language learning and on the relationship between language and cultural identity. With reference to some of the latest findings from brain imaging in learners who speak one, two or more languages, it looks at the physical effects of bilingualism and multilingualism, and how these may be applied in teaching and in school policy to improve education. With reference to a recent survey of students in international secondary schools in Indonesia, it also discusses the cultural aspects of language use in schools and the role of language in identity. It examines the effects of learning more than one language at a young age, and of learning subjects through a language which is not the learner's first language. A large number of schools worldwide currently teach English to speakers of other languages from an early age. This paper discusses the degree to which such early foreign or second language teaching is actually useful or effective. In many parts of the world, it has also become popular to teach mainstream or even all curriculum subjects in English. Some, however, have found this to be detrimental in several ways and have therefore reverted to teaching subjects in their national language. Many are concerned about the possibility that languages with a small number of speakers are doomed to being lost and replaced by a national language, or that their national language could eventually be replaced by English. This could have important repercussions both on local cultures and on international relations, given the emotive aspects of one's first language. Vital decisions on language are frequently made based on the need for English in careers. However, it may be that the current language teaching situation is not actually succeeding in improving students' use of English or their learning in general. Moreover, there is a great risk of producing one or more generations of school leavers and graduates who cannot function beyond everyday conversation in their first language. It may be impossible for English to continue to dominate education without raising affective barriers to learning by giving a low status to local languages and cultures. In this paper, all of the above questions are discussed and researched, and several solutions to the problems arising from them are proposed. Keywords: multilingualism, first language, second language curriculum